SOSIALISASI EDUKASI FAKTOR PENYEBAB KETIDAKDISIPLINAN PESERTA DIDIK SMPN 26 KOTA SERANG TERHADAP PENGGUNAAN SEPATU DAN KAITANNYA DENGAN GANGGUAN SISTEM GANGGUAN SISTEM INTEGUMEN - Siti Aini Rahayu; Mariska Sandrina Oktaviani; Roudhatul Auliya; Mila Ermila Hendriyani (Nindikayla Institute, 2025)
Schools as formal educational institutions certainly have a big in forming national character. School rules and regulations are one of the guidelines for school residents in creating a comfortable and orderly school environment, SMPN 26 Serang City is one of the state junior high schools in Serang City which is located at Kp.Margaluyu, District. Kasemen, Serang City, Banten. One discipline that is the author's focus is discipline in dressing and when most students rarely wear shoes both inside and outside the classroom. SMPN 26 itself has strict regulations relating to discipline, but this behavior of not wearing shoes has become a habit for students.This research also aims to find out the factors that cause students to rarely wear shoes and build the habit of using footwear at school. As a first step, holding outreach regarding the integumentary system and its disorders, this research includes qualitative research with a descriptive type of research with data collection carried out through observation, interviews and questionnaires aimed at students.